2018
DOI: 10.1111/cmi.12889
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniaparasitophorous vacuole membranes display phosphoinositides that create conditions for continuous Akt activation and a target for miltefosine inLeishmaniainfections

Abstract: Miltefosine is an important drug for the treatment of leishmaniasis; however, its mechanism of action is still poorly understood. In these studies, we tested the hypothesis that like in cancer cells, miltefosine's efficacy in leishmaniasis is due to its inhibition of Akt activation in host cells. We show using pharmacologic agents that block Akt activation by different mechanisms and also using an inducible knockdown approach that miltefosine loses its efficacy when its access to Akt1 is limited. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…In addition to TLRs, the induction of CXCL16 involves phosphatidylinositol 3-kinase (PI3K)-AKT signaling (41). Interestingly, it was recently reported that the activity of AKT is sustained during L. donovani infection, which appears to be mediated by phosphoinositides present in the parasitophorous vacuole membrane (42). Consistent with this, we observed that AKT remained phosphorylated in cells infected with WT and lpg1-KOϩLPG1 parasites but was substantially reduced upon infection with lpg1-KO promastigotes (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In addition to TLRs, the induction of CXCL16 involves phosphatidylinositol 3-kinase (PI3K)-AKT signaling (41). Interestingly, it was recently reported that the activity of AKT is sustained during L. donovani infection, which appears to be mediated by phosphoinositides present in the parasitophorous vacuole membrane (42). Consistent with this, we observed that AKT remained phosphorylated in cells infected with WT and lpg1-KOϩLPG1 parasites but was substantially reduced upon infection with lpg1-KO promastigotes (Fig.…”
Section: Resultssupporting
confidence: 83%
“…While GRASP65 is located mainly in the cis part of the Golgi, GRASP55 is present in the medial and trans faces [6,7]. These unique localizations of both GRASPs have been explored as Golgi markers for co-localization experiments in several manuscripts [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale to examine an Akt inhibitor as a potential candidate to treat leishmaniasis came from our recent studies that Leishmania activates Akt signaling in infected cells [ 5 , 7 , 8 ] to promote the persistence of the infection. A few reports have shown that Akt is activated by Leishmania infection and that knock down of Akt limits survival of Leishmania parasites in infected cells [ 6 , 11 , 13 , 18 ] also provided evidence that Akt is the most likely target of miltefosine in Leishmania infections. Together, those studies demonstrated that Akt plays an essential role in Leishmania pathogenesis and that its inhibition is a viable approach to control Leishmania infections.…”
Section: Discussionmentioning
confidence: 99%
“…Akt phosphorylates Ser/Thr residues on a variety of downstream targets including Glycogen Synthase Kinase -3 beta (GSK-3β), Forkhead Box O (FOXO1) and Bcl-2-associated death promotor (BAD), which regulate cellular processes such as cell growth, survival, and metabolism [ 9 , 10 ]. A few reports have shown that Akt is activated by Leishmania infection and that knock down of Akt limits survival of Leishmania parasites in infected cells [ 6 , 11 13 ], which suggests that Akt plays an essential role in Leishmania pathogenesis. Human Akt isoforms share around 98% sequence homology with mouse orthologs predicting relevance of murine models of leishmaniasis to human application.…”
Section: Introductionmentioning
confidence: 99%